Educación estética y lectura semiótica: el caso de un poema de Augusto do Campos (2014)
Given the interest in raising educational paths for the socialization of historical events that have marked the social identity of our actual cultures, this article compiles an analysis of the poem “Hiroshima, mi amor”, the Brazilian poet and essayist Augusto Do Campos in order to develop at least two dimensions, such us: A methodological one, which lets us see the appropriation of the semiotic description, through three levels of intervention, as an effective tool to advance comprehensive readings of high complexity and ambiguity, as in the case of the creative products; and (ii) an ideological one, which includes reflections on the affective nature of the human being and its existence by the way of gender relations. On the assumption that literary texts reflect identificatory aspects of the ways of thinking and behaving, and supported in an inquiry that inserted socio-psychological and anthropological frames, the result of this effort allows us to conclude, on the one hand, the relevance of the semiotic design for the understanding of the cultural textures within a game that joins the poetry and other modern aesthetic experiences and very useful in educational contexts; and, on the other hand, the possibility to advance understandings that show how in the human world the boundaries between life and death, the union and the disunity, remembrance and forgetfulness are porous and communicate each other immediately.